Adding Time into the Mix: Stakeholder Ethics in Qualitative Longitudinal Research. Issue 2 (August 2013) - Neale, Bren
This paper explores the ethical considerations that arise in the conduct of Qualitative Longitudinal (QL) research, drawing on work undertaken as part of the ESRC Timescapes initiative. Adding time into the mix of a qualitative study heightens the need for ethical literacy. Well established ethical principles take on new meaning and need reworking when seen with a temporal gaze – for example, those relating to consent as an ongoing process; sustaining confidentiality when the risk of disclosure is magnified over time; and the ethical representation of lives in the construction, display and re-use of research data. The challenges are magnified in relation to the tenor, flux and recurrent nature of the research process. The elongated time frames for empirical research create long term, reciprocal research relationships that need careful consideration and nurturing over time. More broadly, as QL research unfolds, a wider constituency of individuals and organisations become implicated in the process, necessitating new thinking about their varied needs and claims. QL researchers find themselves navigating through a broader ethical landscape, which this paper seeks to capture through the concept of 'stakeholder' ethics. A stakeholder approach allows for the varied needs of those implicated in the research to be recognised and reconciled, and for a greater appreciation of how research relationships intersect and impact on the research process as it unfolds. Adding time into the mix also enables a distinction to be drawn between pro-active and re-active ethical strategies, both of which are needed in the longer time frames of QL enquiry. The discussion focuses on the conduct of QL research, illustrating the practices of researchers in the field as a starting point for a productive iteration between ethical principles and practice. The paper concludes that time is a complicating factor but also an important resource in the ethical conduct of qualitative research.